Experience report: evolution of a web‐integrated software development and verification environment. (24th February 2014) - Cook, Charles T.; Sun, Yu‐Shan; Sitaraman, Murali
Summary This paper summarizes our experiences over the last 4 years in creating a web‐integrated software development and verification environment. The environment has been used for both research experimentation and education. It has been used in undergraduate computer science courses to teach modular software development and analytical reasoning principles at multiple institutions. In the process, the environment has undergone many refinements to meet demands for improved functionality and to leverage rapidly changing underlying technology for the improvements. The environment is tailored to present formal specifications and alternative implementations of components, and enable correctness checking through a server‐side verifying compiler. This paper presents a detailed account of the development and evolution of the environment—its functionality, user interface, and underlying technology—that we hope will serve as a model for others, especially as the benefits of online learning systems are becoming increasingly obvious. Copyright © 2014 John Wiley & Sons, Ltd.